IMPLEMENTASI HUKUM DAN HAK ASASI MANUSIA DI INDONESIA - Nirwansyah, Nirwansyah (LLDIKTI Wilayah X, 2014)
Ensure legal certainty in the community, is to publish or assign relevant laws. Law is a rule in the form of norms and sanctions, created with the purpose of regulating human behavior, maintain order, justice, and prevent chaos. Each masyarat, is entitled to obtain a defense before the law. Law can be interpreted as a statute or statutes / regulations written or unwritten to regulate peoples lives and provide sanctions for violating it. Man, born in any parts of the world, legally own rights to live. Enforcement of Human Rights (HAM), irrespective of economic status, education, gender, race and other. The concept of human rights, which spearheaded UN Human Rights Commission of Human Rights gave birth to seventeen points stated in the declaration. The declaration or agreement